The Babilili-ritual from Hattusa (CTH 718) - Beckman, Gary M. 1948- (Winona Lake, Indiana Eisenbrauns, 2014)
Contents -- Acknowledgments -- Register of Texts CTH 718 -- Introduction -- The Main Texts: Transliterations -- The Main Texts: Translations -- The Fragments -- The Commentary -- The Incantations -- Bibliography -- Indexes
Includes bibliographical references and indexes. - English translations of Hittite and Akkadian lines, with examples in original languages. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Hittites -- Religion; Akkadian language -- Texts; Hittites -- Religion; Akkadian language -- Texts; BODY, MIND & SPIRIT ; Spirituality ; Paganism & Neo-Paganism; RELIGION ; Comparative Religion; Akkadian language; Hittites ; Religion; Religion; Texts; Kizzuwatna (Cilicia) -- Religion; Kizzuwatna (Cilicia) -- Religion; Electronic books